Effects of interferons alpha and gamma on cytokine production and phenotypic pattern of human bronchial epithelial cells - Stríz, I; Mio, T; Adachi, Y; Carnevali, S; Romberger, D J; Rennard, S I (International journal of immunopharmacology, 2000)
Human bronchial epithelial cells are involved in airway immune mechanisms through secretion of cytokines and through cell-cell contacts with immunocompetent cells. The aim of our study was to assess the ability of interferon (IFN) alpha and gamma alone and in combination to modulate human bronchial epithelial cell (HBECs) release of the inflammatory cytokines IL-8 and IL-6 and fibronectin and to induce the surface expression of HLA-DR and ICAM-1 molecules involved in immune interactions with other cells. HBECs spontaneously secreted a limited amount of IL-8, which was significantly increased by IFN gamma. IFN alpha inhibited IFN gamma stimulated IL-8 secretion in a concentration-dependent manner. Further, IFN gamma induced IL-6 and fibronectin secretion, and this was also inhibited by IFN alpha. The expression of HLA-DR antigens was significantly increased by IFN gamma and partially inhibited by co-stimulation with IFN alpha. In contrast, IFN gamma also induced ICAM-1 expression by HBECs but co-stimulation with IFN alpha had no significant effect on the expression of this surface antigen. IFN alpha modulation of HBEC functions does not seem to be restricted to IFN gamma stimulation since either stimulatory or inhibitory effects of INF alpha on IL-8 production have been found in pilot experiments using IL-1 beta, TNF alpha, and TGF beta as stimuli. In summary, IFN-gamma induces a number of responses in HBECs including increased secretion of IL-6, IL-8 and fibronectin and increased expression of HLA-DR and ICAM-1. IFN alpha can inhibit all these except expression of ICAM-1 which is unaffected. IFN alpha can also interact with other inflammatory cytokines, but whether the effects are inhibitory or augmentive depends on the cytokines.
Keywords: Humans; Interferon-alpha; bronchy; Bronchi; cytokiny; Interleukin-6; Interleukin-8; Phenotype; interleukin-8; epitelové buňky; lidé; Cells, Cultured; HLA-DR antigeny; Fibronectins; HLA-DR Antigens; Epithelial Cells; mezibuněčná adhezivní molekula-1; interleukin-6; fenotyp; kultivované buňky; Cytokines; interferon alfa; interferon gama; fibronektiny; Intercellular Adhesion Molecule-1; Interferon-gamma